Itaconimides as Novel Quorum Sensing Inhibitors of Pseudomonas aeruginosa - Fong, July; Mortensen, Kim T.; Nørskov, Amalie; Qvortrup, Katrine; Yang, Liang; Tan, Choon Hong; Nielsen, Thomas E.; Givskov, Michael (Frontiers in Cellular and Infection Microbiology, 2019)
P. aeruginosa is known as an opportunistic pathogen that often causes persistent infections associated with highly antibiotic-resistance and biofilms formation. Chemical interference with bacterial cell-cell communication, termed quorum sensing (QS), has been recognized as an attractive approach to control infections and address the drug resistance problems currently observed worldwide. Instead of imposing direct selective pressures on bacterial growth, the right bioactive compounds can preferentially block QS-based communication and attenuate cascades of bacterial gene expression and production of virulence factors, thus leading to reduced pathogenicity. Herein, we report on the potential of itaconimides as quorum sensing inhibitors (QSI) of P. aeruginosa. An initial hit was discovered in a screening program of an in-house compound collection, and subsequent structure-activity relationship (SAR) studies provided analogs that could reduce expression of central QS-regulated virulence factors (elastase, rhamnolipid and pyocyanin), and also successfully lead to the eradication of P. aeruginosa biofilms in combination with tobramycin. Further studies on the cytotoxicity of compounds using murine macrophages indicated no toxicity at common working concentrations, thereby pointing to the potential of these small molecules as promising entities for antimicrobial drug development.